ANALISIS HABITAT PENELURAN PENYU LEKANG (Lepidochelys olivacea) PADA KAWASAN TAMAN BURU DATARAN BENA, KECAMATAN AMANUBAN SELATAN, KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Ermelinda Wea Go’o; Ludji Michael Riwu Kaho; Astin Elise Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Bridle turtles belong to endangered species caused by natural events around the habitat of the delineation, theft of turtle eggs, utilization of turtle body parts by humans or the increase of natural predators. The Area of Bena Plain Labor Park is one of the locations of the conservation of the Lekang Turtle species(Lepidochelys olivaceae)but the state of its habitat is not yet known on the beach. This research was conducted with the aim to be able to know the state of the habitat of the lectory turtles (Lepidochelys olivaceae) that has been conducted in August-September 2020. The types of data collected in the form of primary data are beach slope, beach width, sand grain size, natural predator sand surface temperature, vegetation, nest distance from the highest tide limit, depth and diameter of nests and secondary data in the form of nest count data and number of eggs in September 2015-2019. The data is analyzed descriptively qualitatively and descriptive statistics. The results showed that the time of eviction occurs a lot at 23.18 WITA – 00.12 WITA. As for the slope of the beach is classified as tilted and is a suitable slope, the average width of the beach is 34 m, with a range of medium to rough sand grain size. The surface temperature of natural and semi-natural nests are different, the most natural predators are beach crabs and wild dogs, vegetation that dominates marine firs with moderate uniformity value. The average distance from the highest tide limit is 21.2 m, the depth is 42.8 cm, and the diameter is 17.8 cm. So it can be said that the physical condition of the beach of Bena Plain Labor Park as a place where the abandonment of bridle turtles (Lepidochelys olivacea) is in a fairly good condition although there are still some disturbances or threats but can still be resolved.